Optimal estimations of directional wave conditions for nearshore field studies. (15th May 2020) - de Swart, R.L.; Ribas, F.; Calvete, D.; Kroon, A.; Orfila, A.
Abstract: Accurate directional wave conditions at shallow water are crucial for nearshore field studies and necessary as boundary conditions for morphodynamic models. However, obtaining reliable results for all wave parameters can be challenging, particularly regarding wave direction. Here, the accuracy of two global hindcast models and propagation of measured wave conditions using linear wave theory or the SWAN wave model (forced by integrated wave parameters or 2D spectra) is assessed to obtain directional wave conditions at shallow water for Castelldefels beach, northwestern Mediterranean Sea. Results are analyzed using different statistical error parameters and for different wave climates (shore-normal, shore-oblique and bimodal). The analysis shows that global hindcast models correctly predict the trends in wave height and mean wave period but predictions for mean wave direction are only accurate for shore-normal waves. Linear wave theory provides good results for wave height but underestimates refraction, resulting in significant errors in mean wave direction for shore-oblique waves. Finally, SWAN forced with 2D spectra results in the most accurate predictions for all wave parameters. When using integrated wave parameters as boundary conditions, the results for wave height and mean period stay the same whilst the errors in peak period and mean direction worsen for shore-oblique and bimodal wave climates. The reason is that for these wave conditions the directional spectrum constructed out of integrated wave parameters does not resemble the actual directional spectrum. Highlights: Five methods to obtain directional wave conditions at shallow waters are tested. Hindcast models provide proper wave height and period but unreliable wave angle. Propagating idealized buoy-derived spectra still leads to inaccurate direction. Only propagating buoy-measured directional spectra produces accurate wave direction.